Effect of dietary supplementation of tulasi (Ocimum sanctum) and selenium on alanine, transaminase, (ALT) and aspartate transaminase (AST) levels in broilers - L.S.S. Vara Prasad Reddy; V. Leela; A. Thangavel; K.V.S.N. Raju (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The research was carried out to study the effects of dietary supplementation of Tulasi (Ocimum sanctum) and selenium on ALT and AST enzyme levels in broiler chicken. A total of forty-two broiler chicks of day old divided into six groups of seven each were used for this study. Ocimum sanctum leaf powder (0.25% and 0.5%), organic selenium (0.3 ppm) and their combinations were added to the basal diet. Body weight and feed consumption were recorded at weekly intervals. Blood samples were taken at the end of 6th week for enzymological assay from each treatment. The enzymes assayed were alanine transaminase (ALT) and aspartate transaminase (AST). Dietary supplementation of Ocimum sanctum leaf powder at 0.25%, 0.5% levels and its combination (0.5% level) with selenium (0.3 ppm) reduced the levels of ALT and AST significantly (P